EDUKASI MASYARAKAT SEBAGAI UPAYA MITIGASI ABRASI PANTAI DI DESA JUANGA KABUPATEN PULAU MOROTAI PROVINSI MALUKU UTARA - Bayau, Edom; Suhry, Hendro Christi (Universitas Pattimura, 2024)
Juanga Village, South Morotai District, Morotai Island Regency, is one of the areas that is very vulnerable to coastal erosion, this is due to the high sea waves that often occur. Community service activities aim to educate the local community about the importance of planting mangroves as an effort to mitigate the coastal erosion disaster that occurred in Juanga Village. Community service starts from identifying problems that occur, then conducting outreach to the community and carrying out mangrove planting actions in designated areas involving KKNT students at Hein Namotemo University. The result of Community Service is that the community can be educated to continue to maintain natural balance by planting coastal vegetation that can withstand the rate of abrasion, one of which is mangroves because mangrove vegetation is important vegetation for the sustainability of marine biota and as a coast guard from abrasion. It is hoped that with this activity the people of Juanga Village can increase their knowledge and carry out sustainable planting.